2013
DOI: 10.1103/physrevb.87.195315
|View full text |Cite
|
Sign up to set email alerts
|

Optical initialization of hole spins inp-doped quantum dots: Orientation efficiency and loss of coherence

Abstract: We study theoretically the recently proposed hole spin initialization scheme for p-doped quantum well or dot systems via coupling to trion states with sub-picosecond circularly polarized laser pulses. We analyze the efficiency of spin initialization an predict the intrinsic spin coherence loss due to the pulse excitation itself as well as the phonon-induced spin dephasing, both taking place on the timescale of the driving laser pulse. We show that the ratio of the degree of dephasing to the achieved orientatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, the usage of doped structures comes with a number of drawbacks, first of which is the lowering of the material quality (especially optical) caused by the doping as well as problems with proper doping (particularly p-type) of some materials, such as InGaAs [18]. Moreover, it has been shown that there is an intrinsic spin dephasing present in the initialization of resident spins caused both by the temporal excitation to charged excitonic complex states with subsequent recombination itself and by the phonon reservoir reaction to this carrier system evolution, which takes place during the laser pulse [28]. This may be important in future applications but affects also the results of current experiments [29], in particular those based on the resonant spin amplification effect [20,30,31], where the spin coherence is crucial for the formation of the observed signal.…”
Section: Introductionmentioning
confidence: 99%
“…However, the usage of doped structures comes with a number of drawbacks, first of which is the lowering of the material quality (especially optical) caused by the doping as well as problems with proper doping (particularly p-type) of some materials, such as InGaAs [18]. Moreover, it has been shown that there is an intrinsic spin dephasing present in the initialization of resident spins caused both by the temporal excitation to charged excitonic complex states with subsequent recombination itself and by the phonon reservoir reaction to this carrier system evolution, which takes place during the laser pulse [28]. This may be important in future applications but affects also the results of current experiments [29], in particular those based on the resonant spin amplification effect [20,30,31], where the spin coherence is crucial for the formation of the observed signal.…”
Section: Introductionmentioning
confidence: 99%
“…For very large pumping powers, the hole SDT extracted from the data (not shown) decreases slightly, indicating sample heating. A detailed theoretical study of rapid hole spin dephasing, induced by phonons, was performed recently [28].…”
Section: Initialization Of a Hole Spin Polarizationmentioning
confidence: 99%
“…Dynamics of a carrier spin in semiconductor quantum dots (QDs), as well as other semiconductor nanostructures, is a subject of active studies, both theoretical and experimental, due to potential implementations in fields of spintronics and quantum information processing 1,2 . High-fidelity initialization 3,4 , control 5,6 , readout and storage 7 of the information encoded in the spin are essential for future applications. These can be achieved with hole spin due to its relatively long coherence time 8 , which is related to significantly weaker hyperfine interaction as compared to the electron case [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%